KOLABORASI STAKEHOLDER DALAM PENJAMINAN MUTU LEMBAGA PENDIDIKAN ISLAM - Nurhayati, Novia; Zainal Berlian; Arwan (STKIP Subang, 2026)
This research aims to examine the role of stakeholder collaboration in ensuring the quality of Islamic educational institutions. This research uses a qualitative approach with a library research type, with data sources including books, scientific journals, and regulations relevant to the research topic. Data collection techniques were carried out thru documentation studies, while data analysis used qualitative descriptive techniques thru the stages of data reduction, data presentation, and conclusion drawing. The research results show that stakeholder collaboration involving school principals, teachers, students, parents, the government, and the community plays a strategic role in improving the quality of education. That collaboration is able to strengthen the planning, implementation, and evaluation of education oriented toward quality standards. However, there are various challenges in its implementation, such as differing viewpoints, limited time and resources, lack of effective communication, and resistance to change. Therefore, strong synergy, effective leadership, and open communication are needed to optimize stakeholder collaboration. Thus, stakeholder collaboration becomes a key factor in realizing sustainable quality assurance in Islamic education.